DISKURSUS ALAM SEMESTA ORANG LAMAHOLOT DALAM TERANG FILSAFAT ALAM GEORG WILHELM FRIEDRICH HEGEL - Tatap, Eric Yohanis (Studi Budaya Nusantara, 2022)
The discourse on the cosmology or universe has recently received special attention in intellectual circles. This attention arises because the universe is understood by humans differently. The wisdom of Lamaholots, means that the universe is the manifestation of God's self or is referred to as Lera-Wulan Tana- Ekan. In Philosophy, especially for German Idealism, the universe is defined as the place of self-alienation of the Absolute Spirit. From these two different perspectives, researchers want to analyze the meaning of the universe further. This research uses a comparative study method to perform a two-way analysis. The goal is that wisdom and philosophy can act as formal and material objects. His findings are that the universe cannot be denied having different meanings. The universe can be interpreted as a manifestation of the Divine or the Absolute Spirit or vice versa. In addition to these differences, there are also one or two similarities that can be accepted rationally and accounted for.